PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA APARATUR DESA DI KECAMATAN HURUNA KABUPATEN NIAS SELATAN - Waruwu, Agus Ifandi (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
This research was conducted to determine the influence of motivation and discipline on employee performance at the Mazino sub-district office, South Nias Regency. This research is quantitative research that is causal in nature. The population in this study were all employees at the Mazino Subdistrict Office, South Nias Regency, a sample of 30 respondents. The partial hypothesis test results show that the value of t_count>t_table, and the significance level is 0.000<0.05, then H_a is accepted and H_0 is rejected, meaning that the variable discipline (X1) and the motivation variable (X2) have a positive and significant effect on employee performance (Y) . The coefficient of determination (R^2) is 0.975 (75%) so it can be shown that 75% of the variation in the dependent variable is explained by the independent variable, while the remaining 24.9% is the variable outside the model. The conclusion from this research is that motivation and discipline are the main factors in achieving good performance, and as a suggestion from the author, namely, To improve employee performance, leaders should be more able to participate actively in every activity or group work and provide motivation to employees so that all work can be carried out. well.